2019
DOI: 10.3389/fphar.2019.00733
|View full text |Cite
|
Sign up to set email alerts
|

C-Phycocyanin Ameliorates Mitochondrial Fission and Fusion Dynamics in Ischemic Cardiomyocyte Damage

Abstract: Mitochondrial dysfunction is a predominant risk factor in ischemic heart disease, in which the imbalance of mitochondrial fusion and fission deteriorates mitochondrial function and might lead to cardiomyocyte death. C-phycocyanin (C-pc), an active component from blue-green algae, such as Spirulina platensis , has been reported to have anti-apoptosis and anti-oxidation functions. In this study, the effects of C-pc on mitochondrial dynamics of cardiomyocytes was examined using an oxygen–gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…The mammalian mitochondrial genome has 37 genes, 13 of which encode polypeptide subunits of enzyme complexes of the oxidative phosphorylation system, which provides more than 95% of the myocardial energy requirement for adenosine triphosphate (ATP) production [ 16 , 17 ]. Mitochondria are the main organelles that mediate the energy production and apoptosis of cardiomyocytes [ 18 , 19 ]. Because of the high energy requirement of myocardial cells, MQC is very important in these cells.…”
Section: Mqcmentioning
confidence: 99%
“…The mammalian mitochondrial genome has 37 genes, 13 of which encode polypeptide subunits of enzyme complexes of the oxidative phosphorylation system, which provides more than 95% of the myocardial energy requirement for adenosine triphosphate (ATP) production [ 16 , 17 ]. Mitochondria are the main organelles that mediate the energy production and apoptosis of cardiomyocytes [ 18 , 19 ]. Because of the high energy requirement of myocardial cells, MQC is very important in these cells.…”
Section: Mqcmentioning
confidence: 99%
“…On the other hand, our results showed that caloric restriction enhanced the relative expression of Nrf1/Tfam/Mgmt and ATP5A1 network in the heart tissue. In this regard, studies have shown that resistance training and a caloric restriction increased mitochondrial fission protein (Opa1 and Mfn1) and PGC-1α expression in the skeletal muscle of rats (Gao et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, further studies are necessary to better understand how signaling via both estrogen and testosterone influence cardiac apoptosis in CVD. Necrosis and pyroptosis are inflammatory cell death pathways regulated via caspase enzyme activity, which is induced when irreversible damage occurs in the tissues ( Bergsbaken et al, 2009 ; Gao et al, 2019 ; Zhaolin et al, 2019 ). These pathways, more specifically, are initiated when the MPTP is damaged or uncontrolled in mitochondrial fission, as seen in CVD ( Song et al, 2015 ; Amgalan et al, 2020 ).…”
Section: Cell Deathmentioning
confidence: 99%